PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA MODEL LEARNING CYCLE 5E PADA MATERI INTEGRAL DI KELAS XII IPA (Jurnal Ilmiah Soulmath : Jurnal Edukasi Pendidikan Matematika, 2016)
This research is development, aims to describe the process and produce a goodlearning tool development with learning cycle 5E models on material integral in class XII IPA. Process of learning tool development used in this research is modification of learning tool development model according to Thiagarajan, Semmel & Semmel consisting of definition phase, design phase, development phase, and dissemination phase. But in this research is until the development phase only without conducting dissemination. Learning device produced in the form of: (1) Lesson Plan (RPP), (2) Student Worksheet (LKS), and (3) Learning Outcomes (THB). Beside of learning documents research instruments used were validation sheets of learning documents, observation sheet of teacher skills in learning management, students activity observation sheets, and questionnaire for students responses. As for the criteria of a good learning device meets three aspects: (1) valid, (2) practical, and (3) effective. Based on test result obtained that the learning documents of Learning Cycle 5E models are in good quality and meets three aspects: (1) valid, (2) practical, and (3) effective. (1) declared valid by the validator and the learning outcomes test meet the criteria for a valid, reliable, and sensitive, (2) practical, which is expressed by the average value of learning is the ability of teachers to manage a minimum of four, so that means the ability of teachers to manage learning is good, and (3) effective, which is of the students response positive a learning component and classical learning completeness reached.Keywords: Development Equipment, Learning Cycle 5E, Integral